Nego veio é um sofrer : uma etnografia da subalternidade e do subalterno numa irmandade do Rosário - Silva, Bruno Goulart Machado (2012)
The object of this work is a fellowship of São Sebastião e Nossa Senhora do Rosário in the city of Jardim do Seridó (RN), that is, a black catholic fellowship on the sertão potiguar. The devotion to Nossa Senhora do Rosário, in colonial Brazil, organizes itself through black catholic men as fellowships. They blossomed in Brazil until the abolition, getting support from the Catholic church, from owners of slaves and from the population in general − unlike others afro-Brazilian religious expression. Today, these fellowships remain active, against the sentimental pessimism of the folklore studies, and they also have a highlight position in the calendar of many cities in Brazil, and in particular in Seridó. The research s foothold is the apparent valorization of the fellowship by the local elite, attitude that hides asymmetric relationships between the group of negros do Rosário and the local authorities, having as its consequence that the members occupy a subaltern position inside their own fellowship. This subalternity take place, mainly, in the public area, where the negros do Rosário cannot represent themselves neither political nor discursively. To discuss this idea, it s done a brief historical of these catholic institutions as well as a description of the relationship between the negros do Rosário and the elites of the city. Then, the phenomenon is analyzed as folklore and/or religion , under the perspective of many agents that participate in this process. In other moment, it is going to be presented how the group formulates their own representation of the history, of the devotional forms and of their own political-religious experiences. In this sense, an ethnography of the subalternity is understood as an analysis of the process that leads the negros do Rosário to become a subaltern group. It s also outlined the perception that the group has of its own position, through an ethnography essay of the subaltern subject. The research, focused in the group of Rosário, was done between August 2010 and January 2012 and includes other agents (like treasurers, priests and intellectuals). Besides that, as a methodological complement, there are documental research, photography, as well as shoots of the party days and public presentation